Mental Diseases According to Hamka and the Methods of Treatment (A Review of Hamka's Tasawuf Modern Book) - Imroatul Istiqomah; Fikri Hidayatul Rukmana; Muhammad Shohibul Mujtaba (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This study aims to answer the challenges of modern psychology with Hamka's soul theory in his book Tasawuf Modern. This is a qualitative study conducted at a library that analyzes data using descriptive analytical methods, psychological and Sufi approaches, and deductive-inductive techniques. The findings of this study are: first, the definition and characterization of a healthy soul according to Hamka and its hierarchy. Second, according to Hamka, mental illness is in the form of ghadab, takabbur, khauf and huzn and their triggers. Third, the treatment of mental illness is by coaching the soul through tadzkiatu al-nafs externally, namely: 1) associating with good people, 2) getting used to thinking, 3) maintaining lust, 4) working regularly, 5) self-introspection. And internally, namely sincerity, gratitude, asceticism, resignation and qana'ah. From this research we can understand that mental health is the influence of the purity of the soul through the education of the mind and heart externally and internally.